Love for Prophet Muhammad (Part Two): moral obligation and spiritual need - Hasan, Md. Mahmudul (OnIslam.net, 2008)
Love for Prophet Muhammad is an obligation for all Muslims. This may sound oxymoronic, as obligatory love may not be considered true love. However, this love is still a moral obligation that arises from an intrinsic deep connection between us; the believers and him; our beloved one. This obligation is, thus, embraced — it is not imposed on Muslims. In fact, this obligation is slightly different from other forms of religious duties. Many Muslims are negligent in carrying out their religious duties and rituals, yet there is a deep-seated love for the Prophet in their hearts. In fact, Muslims' love for him is unique; it is more than a mere obligation. However, the Prophet never allowed Muslims to exceed their limits when they show their love for him.